An empirical investigation of the news effects in Turkish financial markets - Nazipova, Zilya (My University, 2005)
The main aim of this thesis is to investigate the effects of news effect on the Turkish financial markets. To this end, first of all, this thesis investigates the impacts of eleven types of macroeconomic announcements and three types of monetary authority actions on the Turkish bond, the Turkish National ISE-30 financial stock and the TL/ USD exchange rate markets. Second, this study analyses the effects of political news, the National Security Council announcements on these markets. Beyond documenting the effective news and events on the markets, the significance of these news and events over time is also tested. Finally, this thesis investigates the effectiveness of the Central Bank interventions on the TL/ USD exchange rate market. To estimate the impacts of news and events on the daily Turkish financial markets during the period from April 1, 2001 to April 30, 2004 the popular ARCH-type models are applied. The results of this thesis suggest that the effects of macroeconomic announcements and monetary authority actions are not permanent over time. The news and events effects are found to be very variable over time. Furthermore, this thesis finds that the Central Bank interventions on the TL/ USD exchange rate markets not effective. nancial markets, news effect, macroeconomic announcements, Central Bank intrventions. tezin amacı çeşitli haberlerin Türk finansal piyasalarına etkisini incelemektir. Bunun için, öncelikle onbir farklı makro ekonomik haberlerin ve üç farklı parasal otorite kararları uygulamalarının Türk bono, Türk İMKB-30 borsa endeksi ve TL/ Dolar piyasalarına etkileri incelenmiştir. Burada ayrıca, Milli Güvenlik Konseyi toplatı kararları açıklamalarının Türk finansal piyasalarına etkileri de incelenmiştir. Çalışma ayrıca sözkonusu haberlerin ve olayların zaman içerisinde etkinliklerini de test etmiştir. Son olarak, TL/ Dolar piyasasına yapılan Merkez Bankası müdahalelerinin etkinliği incelenmiştir. Bu çalışma, Nisan 2001 - Nisan 2004 zaman dilimini kapsamaktadır. Bu çalışmada ARCH tipi modeller kullanılmıştır. Tez makroekonomik haberler ve parasal otorite kararları etkilerinin Türk finansal piyasalarında kalıcı olmadığını bulunmuştur. Bu çalışma ayrıca TL/ Dolar piyasasına yapılan Mekez Bankası müdahaleleri piyasa üzerinde etkili olamadığını bulmuştur. nansal Piyasalar, Haberlerin Etkisi, Makroekonomik Haberler, Merkez Bankası Müdaheleleri
Keywords: Ekonomi; Finansal Pazarlar; Finansman ekonomisi